2022
DOI: 10.1021/acs.nanolett.2c02057
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced High Thermal Conductivity Cellulose Filaments via Hydrodynamic Focusing

Abstract: Nanocellulose is regarded as a green and renewable nanomaterial that has attracted increased attention. In this study, we demonstrate that nanocellulose materials can exhibit high thermal conductivity when their nanofibrils are highly aligned and bonded in the form of filaments. The thermal conductivity of individual filaments, consisting of highly aligned cellulose nanofibrils, fabricated by the flow-focusing method is measured in dried condition using a T-type measurement technique. The maximum thermal condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have revealed that bulk lms comprising structurally regular biopolymers, such as nanocellulose, lamentous viruses, and designed tandem-repeat proteins, are promising thermally conductive materials. 19,20,[23][24][25][26][27][28][29][30] The chemical cross-linking of SF materials has recently been used in addition to physical cross-linking, through the formation of crystalline antiparallel b-sheets, to improve and/or pioneer physicochemical properties and functions. With relatively high amounts of Tyr residues in SF (Tyr: 5.3 mol% Gly: 45.9 mol%, Ala: 30.3 mol%, Ser: 12.1 mol%, and Val: 1.8 mol%), 31,32 it was reported that the oxidation of adjacent Tyr residues by horseradish peroxidase or ultraviolet (UV) light irradiation resulted in chemically cross-linked SF by the effective formation of dityrosine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that bulk lms comprising structurally regular biopolymers, such as nanocellulose, lamentous viruses, and designed tandem-repeat proteins, are promising thermally conductive materials. 19,20,[23][24][25][26][27][28][29][30] The chemical cross-linking of SF materials has recently been used in addition to physical cross-linking, through the formation of crystalline antiparallel b-sheets, to improve and/or pioneer physicochemical properties and functions. With relatively high amounts of Tyr residues in SF (Tyr: 5.3 mol% Gly: 45.9 mol%, Ala: 30.3 mol%, Ser: 12.1 mol%, and Val: 1.8 mol%), 31,32 it was reported that the oxidation of adjacent Tyr residues by horseradish peroxidase or ultraviolet (UV) light irradiation resulted in chemically cross-linked SF by the effective formation of dityrosine.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that bulk films comprising structurally regular biopolymers, such as nanocellulose, filamentous viruses, and designed tandem-repeat proteins, are promising thermally conductive materials. 19,20,23–30…”
Section: Introductionmentioning
confidence: 99%